Building a terrorist house on sand: a critical incident analysis of interprofessionality and the Prevent duty in schools in England - Lundie, David (Journal of beliefs and values, 2019)
In 2015, a duty came into effect requiring all public bodies, including schools, to engage with the UK Government's Prevent counter-terrorism strategy. This article presents two case studies from mid-size English cities, exploring the moral prototypes and institutional identities of professional mediators who made schools aware of their duties under Prevent. Mediators in each case included serving and former police, teachers and policy advisers, the majority of whom are now private consultants or operating small 3rd sector agencies. Drawing from in-depth interviews with 14 professionals, the article details the ways in which participants constructed their relationship to normative, deliberative and legal obligations. The article focuses on the recurrence of a high profile critical media incident in which a young child was allegedly subject to a referral for writing about living in a 'terrorist' (rather than 'terraced') house. Reaction to this incident was archetypal of the fear of media moral panic in reconstituting mediators' identities as Prevent professionals, illustrating how the enframing of events shifts professional moral codes, policy interpretation and implementation.